Evaluation of Four Commercial Kits for SARS-CoV-2 Real-Time Reverse-Transcription Polymerase Chain Reaction Approved by Emergency-Use-Authorization in Korea - Hur, Kyu-Hwa; Park, Kuenyoul; Lim, Youngkuen; Jeong, Yun Sil; Sung, Heungsup; Kim, Mi-Na (Frontiers in Medicine, 2020)
SARS-CoV-2 real-time reverse-transcription PCR (rRT-PCR) is the most effective testing system currently available to counter COVID-19 epidemics when potent treatments and vaccines are unavailable. Therefore, four SARS-CoV-2 rRT-PCR kits have been approved by the emergency-use-authorization (EUA) without clinical validation in Korea until March 15, 2020. This study evaluated the analytical and clinical performance of these kits. Allplex 2019-nCoV Real-time PCR (Seegene, Seoul, Korea), PowerChek 2019-nCoV (KogeneBiotech, Seoul), Real-Q 2019-nCoV Real-Time Detection (BioSewoom, Seoul) and StandardM nCoV Detection (SD BIOSENSOR, Osong, Korea) were evaluated. The limit of detection (LODs) of Allplex, PowerChek, and Real-Q was determined by testing the transcribed RNA of SARS-CoV-2 E and the RNA of SARS-CoV Frankfurt1. A total of 27 consecutive samples comprising 13 sputum, 12 nasopharyngeal swab (NPS), 1 urine and 1 stool sample were collected from 2 COVID-19 patients for sensitivity analysis. Precision was assessed via daily tests of positive and negative controls in each kit for 5 d. Reproducibility was examined by repeating 21 samples and 10 fold dilutions of 14 samples in pairs using Allplex. Specificity was evaluated with 24 other respiratory virus-positive samples. LOD of Allplex, PowerChek, and Real-Q were 153.9, 84.1, and 80.6 copies/mL, respectively. The degrees of association between Cts and log viral concentrations by Allplex and PowerChek was expressed as y = -3.319 log (x) + 42.039 (R = 0.96) and y = -3.392 log(x) + 43.113 (R = 0.98), respectively. One or more of the 4 kits detected twenty out of 27 clinical samples positive. Of the 20 positive samples, the detection rates of positives for Allplex, PowerChek, Real-Q, and StandardM were 90.0%, 82.3%, 75.0% and 100.0%, respectively, but those of PowerChek and Real-Q would be 100% if out-of-cutoff Cts were counted as positives. Precision was 100%. Interpretation of Allplex results was reproducible when Ct of E ≤33. All 4 kits showed no cross-reactivity with other respiratory viruses. Performance of the 4 kits indicated the suitability of these for diagnosis and follow-up testing of COVID-19. Laboratory doctors who initially implement these EUA kits must be able to interpret quality control parameters.